Varietal trials and yield components determining variation among okra varieties (Abelmoschus esculentus L.) - Yadav, Shubh Pravat Singh; Bhandari, Sujan; Ghimire, Netra; Nepal, Sudikshya; Paudel, Prava; Bhandari, Tika; Paudel, Pragya; Shrestha, Samaz; Yadav, Bishnu (Future Science, 2023)
Yield analysis is necessary to test the overall performance of different okra varieties. For this, field experiments were performed during the summer season to assess the yield or production of different okra varieties under open field conditions. The experiment comprised four treatments with seven replicas in an RCBD. The treatments included four different varieties of okra: Arka Anamika, Chiranjeevi F1, Gunjan, and JK 1666. The experimental results showed that the average mean yield of four okra varieties was 98.30 gm per plant. Overall, it was further revealed that Arka Anamika gave the highest yield (101.01gm), followed by Gunjan (98.89gm), Chiranjeevi F1 (96.95gm), and JK1666 (96.37gm). Similarly, other parameters were also analyzed simultaneously to check yield attributing factors which unveiled that plant height was maximum (162.55 cm) in Chiranjeevi F1, followed by Gunjan, JK 1666, and Arka Anamika. Moreover, the number of primary branches was highest for Chiranjeevi F1 (4.47). Contrary to this, the number of pods per plant was also the most significant (3.80) in Arka Anamika. Further, Gunjan topped all the other three varieties in terms of pod diameter (5.53 cm) and weight of pod (25.12 gm). The pod length was highest in JK 1666 (14.83 cm). The data from the experiment also demonstrated that Arka Anamika matured faster (50 DAS) than the other three varieties, which showed Arka Anamika to be more economical for farmers; hence, from our field research, it can be inferred that Arka Anamika is a good variety for farmers growing okra in the Morang area.